2012
DOI: 10.1353/csd.2012.0032
|View full text |Cite
|
Sign up to set email alerts
|

First-Generation Undergraduate Students and the Impacts of the First Year of College: Additional Evidence

Abstract: Using longitudinal data from the Wabash National Study of Liberal Arts Education, our findings suggest that first-generation students are at a significant disadvantage across cognitive and psychosocial outcomes compared to students whose parents have at least some postsecondary education. Furthermore, we tested for the conditional effects of good practices on first-year outcomes and found that effects of good practices on both cognitive and psychosocial outcomes differed in magnitude, and sometimes in directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 52 publications
3
89
0
3
Order By: Relevance
“…Institutional variables that improve persistence include high quality and frequent student interactions with faculty members, the availability of academic advising, as well as an explicitly stated university mission that commits to student success (Kuh, Kenzie, Buckley, Bridges, & Hayek, 2006;National Survey of Student Engagement, 2014;Pascarella & Terenzini, 2005). Student variables that increase persistence include being female and having parents with a university education (Dennis, Phinney, & Chuateco, 2005;Finnie, Childs, & Qiu, 2010;Finnie & Qui, 2009;Kuh et al, 2006;Padgett, Johnson, & Pascarella, 2012). While students discontinue university studies for many reasons (most commonly because they do not like it; Finnie et al, 2010), the strongest proximate predictor of retention is academic grades (Gershenfeld, Hood, & Zhan, 2016;Kuh et al, 2006;Pascarella & Terenzini, 2005;Wintre & Bowers, 2007).…”
mentioning
confidence: 99%
“…Institutional variables that improve persistence include high quality and frequent student interactions with faculty members, the availability of academic advising, as well as an explicitly stated university mission that commits to student success (Kuh, Kenzie, Buckley, Bridges, & Hayek, 2006;National Survey of Student Engagement, 2014;Pascarella & Terenzini, 2005). Student variables that increase persistence include being female and having parents with a university education (Dennis, Phinney, & Chuateco, 2005;Finnie, Childs, & Qiu, 2010;Finnie & Qui, 2009;Kuh et al, 2006;Padgett, Johnson, & Pascarella, 2012). While students discontinue university studies for many reasons (most commonly because they do not like it; Finnie et al, 2010), the strongest proximate predictor of retention is academic grades (Gershenfeld, Hood, & Zhan, 2016;Kuh et al, 2006;Pascarella & Terenzini, 2005;Wintre & Bowers, 2007).…”
mentioning
confidence: 99%
“…The ALAS-R might prove to be of value in identifying students most likely to experience a mismatch between perception and experience. Similarly, first-generation college students have been reported to be at a disadvantage in the cognitive and psychosocial development associated with a liberal arts education (e.g., Padgett, Johnson, & Pascarella, 2012). Further research with the ALAS-R could be useful in this regard.…”
Section: Summary and Concluding Discussionmentioning
confidence: 99%
“…They suggested that first-generation students have a more difficult transition to college and are confronted with multiple issues related to cultural, social and academic transition. First-generation students report feeling less prepared for and knowledgeable about college and more worried about failing than continuing generation students (Aspelmeier et al, 2012;Padgett, Johnson, & Pascarella, 2012). Aspelmeier et al (2012) highlighted two studies that indicated only modest differences in adjustment to college between first-and continuing-generation students; however, they concluded that even small effects may have 'practical significance when they reflect serious outcomes that are relevant to large proportions of the population'(p. 758).…”
Section: United States Research On First-generation Studentsmentioning
confidence: 99%
“…Nunez et al (1998) reported that first-generation students were 40% more likely to drop-out of college within five years than their continuing-generation peers. First-generation students exhibit greater confusion regarding expectations related to academic workload and assessment (Collier & Morgan, 2008); are less likely to seek help from faculty (Jenkins, Miyazaki, & Janosik, 2009); and may not gain maximum benefit from interacting with faculty (Padgett et al, 2012).…”
Section: United States Research On First-generation Studentsmentioning
confidence: 99%